Práticas letradas no 5º ano do ensino fundamental: uma experiência com projeto de letramento em língua portuguesa - Andrade, Maria José de (2020)
The stages of a literacy project and the knowledge that is shared with its development should be associated to the daily routine of a student, in order to make sense and he may participate of the activities, comprehending and reflecting about diverse situations which interfere in his growing as a citizen who participates and interacts in society. This way, the present research has as its main objective to comprehend how the development of a literacy project can contribute to the citizen formation of students of the 5th grade Elementary School and to the reframing of their discursive positions in relation to the social problems of the community they are inserted in, by means of the production of two textual genres: open letter and leaflet. In order to substantiate the research about the notion of literacy and literacy projects, it is started from the studies of Street (2014), Soares (2012, 2008), Kleiman (2010, 2007, 2005, 1995), Lotsch (2016), Oliveira et al (2014), Oliveira and Santos (2012), Tinoco (2013, 2008), Dias (2016), Kleiman et al (2013), Santos (2012), among others who understand that working with literacy projects enables the reframing of work with practices of reading and writing. In relation to the notion of writing, the theoretical foundation used the studies of Koch and Elias (2015), Antunes (2010, 2003), Marcuschi (2008), Geraldi (2002), Ferrarezi Junior and Carvalho (2015), as well as what standardizes the Curricular Common National Basis – BNCC (BRASIL, 2018). These authors understand that the social practices of writing require differentiate actions that promote the comprehension and the meaning of the Portuguese Language classes. In relation to studies about textual genres, the research started from Bakhtin (2011), Marcuschi (2008), Antunes (2010), BNCC (BRASIL, 2018) and the National Curriculum Parameters – PCN (BRASIL, 1998). The studies of Brito (2015), Martins (2015), Leite (2014) and Maior (2011) were specifically used about open letter. In relation to leaflet, the studies of Rodrigues (2014) and Karwoski (2005) were considered. The developed research is qualitative and descriptive, delineated as a action research, constituted of steps and a literacy project developed from conversation circles, field class, lecture, and textual productions of the genders open letter and leaflet. All the developed stages were essential to enable students a critical position about the social problem in focus: the accumulated waste along the community streets. This way, the research results point out significant advances in social literacy of students and the resizing of their positions along the project development, from the production of written textual genres and after their insertion in literacy events that propitiate a significant knowledge about the care about environment, especially the waste which is daily produced in our houses.